Magnetization dynamics in an exchange-coupled NiFe/CoFe bilayer studied by x-ray detected ferromagnetic resonance. (15th January 2015) - Stenning, G B G; Shelford, L R; Cavill, S A; Hoffmann, F; Haertinger, M; Hesjedal, T; Woltersdorf, G; Bowden, G J; Gregory, S A; Back, C H; Groot, P A J de; Laan, G van der
Abstract: Exchange-coupled hard and soft magnetic layers find extensive use in data storage applications, for which their dynamical response has great importance. With bulk techniques, such as ferromagnetic resonance (FMR), it is difficult to access the behaviour and precise influence of each individual layer. By contrast, the synchrotron radiation-based technique of x-ray detected ferromagnetic resonance (XFMR) allows element-specific and phase-resolved FMR measurements in the frequency range 0.5–11 GHz. Here, we report the study of the magnetization dynamics of an exchange-coupled Ni0.81 Fe0.19 (43.5 nm)/Co0.5 Fe0.5 (30 nm) bilayer system using magnetometry and vector network analyser FMR, combined with XFMR at the Ni and Co L 2 x-ray absorption edges. The epitaxially grown bilayer exhibits two principal resonances denoted as the acoustic and optical modes. FMR experiments show that the Kittel curves of the two layers cannot be taken in isolation, but that their modelling needs to account for an interlayer exchange coupling. The angular dependence of FMR indicates a collective effect for the modes of the magnetically hard CoFe and soft NiFe layer. The XFMR precessional scans show that the acoustic mode is dominated by the Ni signal with the Co and Ni magnetization precessing in phase, whereas the optical mode is dominated by the Co signal with the Co and Ni magnetization precessing in anti-phase. The response of the Co signal at the Ni resonance, and vice versa, show induced changes in both amplitude and phase, which can be ascribed to the interface exchange coupling. An interesting aspect of phase-resolved XFMR is the ability to distinguish between static and dynamic exchange coupling. The element-specific precessional scans of the NiFe/CoFe bilayer clearly have the signature of static exchange coupling, in which the effective field in one layer is aligned along the magnetization direction of the other layer.